An Evaluation of Selective Foreign e-Bookshops - Khan, Imran (DESIDOC Journal of Library & Information Technology, 2014)
Following the methodology of case comparison, five major foreign e-Bookshops have been evaluated in the present study in the light of the needs and requirements of modern academic libraries. The evaluation criteria consisting of variables like Statement of Collection, Help Menu, Shopping Procedure, Payment Modes, Special Facility provided for Online Purchase, User Search Support, Details of Product, Navigation Links and Special Discounts has been used. The e-Bookshops have been ranked based on the marks obtained for the facilities provided and offered by them. http://dx.doi.org/10.14429/djlit.34.6255